Pengaruh Profitabilitas Dan Pertumbuhan Perusahaan Terhadap Struktur Modal Dengan Ukuran Perusahaan Sebagai Variabel Moderating - Safitri Safitri; Akhmadi Akhmadi (Sains: Jurnal Manajemen dan Bisnis, 2017)
The purpose of this research was to analyze the influence of profitability and company growth to capital structure with company size as moderating variables. Profitability analyzed use trade off theory perspective and company growth analized use pecking order theory perspective. Hyphothesis testing using moderate regression. The population of this research is agronomy company listed in Indoensia Stock Exchange. Sampling methid use purposive sampling which cinsist of 63 sample during 2010 until 2015. The data used in this research is secondary data. Statistic test show that profitability has a positive and significant influence to the capital structure. The statistic testing show that company growth has a positive and significant influence to the capital structure. Hyphothesis testing show that company size able to moderate the relationship between profitability to the capital structure. Hyphothesis testing also show that company siza able to moderate the relations between company            growth                             and                             capital                              structure.